Evaluation of The Rahong Pangalengan Pine Forest Tourism Area - Chaerani, Muthia; Alhamdani, Sania Zaciska; Rahmah, Syifa Alia; Asyiawati, Yulia; Fardani, Irland (Poltanesa, 2024)
Natural tourism areas have an important role in preserving nature and encouraging local economic growth. However, uncontrolled tourism growth often causes environmental problems. Therefore, evaluating the sustainability of tourist area development is very important to ensure long-term natural sustainability, by paying attention to aspects of attractions, amenities and accessibility (3A). This research aims to evaluate the condition of the Rahong Pine Forest tourist area to support sustainable development of the area in the future. The approach used is an interdisciplinary approach that combines ecological, social and economic analysis in regional development. The research results show that the Rahong Pine Forest Tourism Area is included in the very high category. This shows that this area has great potential for natural tourism, but there are still challenges in maintaining a balance between tourism development and environmental conservation. From the research results, there are several recommendations to increase the sustainability of the development of the Rahong Pangalengan Pine Forest tourist area in the future. First, provide clear directions to the area to facilitate accessibility for tourists. Second, provide adequate transportation to the area. Third, improve road infrastructure in tourist areas to ensure comfort and safety. With these steps, it is hoped that the development of the Rahong Pine Forest tourist area can be carried out in a sustainable manner, providing economic benefits for local communities, while preserving the natural environment which is the main attraction of this area.